Outstanding Enrofloxacin Removal Using an Unmodified Low-Cost Sorbent Prepared from the Leaves of Pyracantha koidzumii - Rubén Martínez-Escutia; Abraham Méndez-Albores; Alma Vázquez-Durán (MDPI AG, 2022)
Increasing discharges of synthetic antimicrobial agents from industrial and municipal sewage, as well as from agricultural runoffs into water bodies, is still a global challenge. Here, an unmodified low-cost sorbent was prepared in an ecofriendly manner from Pyracantha koidzumii leaves for the removal of enrofloxacin (ENR). Sorbent characterization was accomplished using Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDS), BET surface area, zeta potential, and point of zero charge. Biosorption assays were carried out via batch mode concerning the impact of adsorbent dosage, contact time, solution pH, solution ionic strength, adsorbate concentration, and temperature. In general, ENR adsorption was significantly correlated with pH and ionic strength. At a neutral pH, the sorbent had a theoretical maximal ENR uptake of 138.89 mg/g. However, the adsorption capacity was significantly affected by the presence of high concentrations of divalent cations (Ca2+ and Mg2+). The findings from the kinetics and isotherms showed that the pseudo-second-order kinetic and Langmuir isotherm models best fit the experimental data. Electrostatic interactions, hydrogen bonding, and π-π stacking were the most important mechanisms of adsorption of ENR onto the P. koidzumii sorbent. Overall, this study suggests the promising application of this agricultural residue for the efficient removal of ENR from water.